Preparation of 1 μm thick Y-doped HfO2 ferroelectric films on (111)Pt/TiOx/SiO2/(001)Si substrates by a sputtering method and their ferroelectric and piezoelectric properties. (4th March 2021) - Shimura, Reijiro; Mimura, Takanori; Tateyama, Akinori; Shimizu, Takao; Yamada, Tomoaki; Tanaka, Yoshitomo; Inoue, Yukari; Funakubo, Hiroshi
Abstract: Y-doped HfO2 films with thicknesses of 150−1000 nm were prepared on Pt/TiO x /SiO2 /Si substrates by the sputtering method and subsequent heat treatment at 800 °C. XRD analysis showed that the films consisted of an almost pure orthorhombic/tetragonal phase. Hysteresis loops originating from the ferroelectricity were observed in the polarization−electric field relationship; the remnant polarization and coercive field were about 12  μ C cm −2 and 1.2 MV cm −1, respectively. Piezoelectricity was also confirmed from the strain−electric field curves for 1  μ m thick films, and the apparent piezoelectric coefficient, d 33, f, near 0 MV cm −1 was estimated to be about 2.5 pm V −1 . Taking account of the relatively low dielectric constant of about 23, the piezoelectric responses from 1  μ m thick films prepared by the sputtering method are useful for piezoelectric microelectromechanical system applications, especially for sensor applications, since the performance of such applications is proportional not only to the piezoelectric response but also to the inverse of the relative dielectric constant.